Altruistic Leadership Reduces Knowledge Hiding Behavior: Mediating Role of Workplace Friendship (Journal of Social Sciences Review, 2024)
This paper explores the relationship between altruistic leadership and knowledge hiding in the workplace, with workplace friendship as the moderator. This paper established that altruistic associations help leaders to build trust, cooperation, and ethical behavior from followers. The study investigates the mediating role of altruistic leadership and addresses the focal construct's direct impact on decreasing knowledge hiding. This work underscores the significance of friendships at the workplace as the primary mode through which such changes happen. Using a cross-sectional quantitative research design, data were gathered from 291 participants in private banks. There is also evidence that altruistic leadership minimizes knowledge hiding both directly and indirectly, with organizational friendships promoting transparency within and eliminating rivalry, which is a key cause of knowledge concealment. This paper adds to leadership literature by providing empirical evidence for the positive effects that altruistic leadership has on collaboration and openness in the workplace and the negative effect that it has on knowledge hiding. The implications indicate that organizations should allow their workers to engage in altruistic behaviors and establish workplace friendships so that they foster information sharing and reciprocal working relationships to support the generation and dissemination of knowledge in organizations, particularly in knowledge-intensive industries like the banking industry.
Keywords: Altruistic Leadership; Knowledge-hiding; Workplace Friendship; SEM-PLS